PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP KEMAMPUAN MENELAAH TEKS FABEL - Sari, Vina Nur Indah; Mering, Aloysius; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of the snowball throwing learning model on the ability to analyse fable texts. While the specific objectives of this study are 1) knowing the difference between snowball throwing learning models and conventional learning models; 2) knowing the difference in high group learning outcomes and low group learning outcomes; 3) knowing the interaction between learning models and learning outcomes on the ability to analyse fable texts. This study used a factorial design experimental method. The population in this study was students of Muhammadiyah Pontianak 1 Secondary School. The sample in this study was seventh grade students of Muhammadiyah 1 Pontianak Secondary School. The techniques of data collection in this study were measurement techniques with multiple choice test instruments, structured observation techniques, and documentation techniques. The results showed that there was a difference in the ability to examine the fable text treated between the snowball throwing learning model and the conventional learning model with Fcount > Ftable (13,377 > 4.03).Keywords: Conventional, Fable Text, Snowball Throwing